Design of a Mathematics Learning Platformer Game Using Unity 2D: Desain Permainan Platformer Pembelajaran Matematika Menggunakan Unity 2D - Handayani, Nana Nur Dwi; Taurusta, Cindy; Astutik, Ika Ratna Indra; Azizah , Nuril Lutvi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Mathematics learning in early grades often faces low student interest, requiring innovative media. Specific Background: Game-based learning is widely used to increase engagement, yet platformer-based mathematics games for young learners remain limited. Knowledge Gap: Existing studies rarely integrate structured level progression and question-based scoring within elementary-level math games. Aim: This study aims to develop a 2D platformer game, “Math With Elysia,” using Unity to support basic mathematical understanding. Results: The game was developed using the Multimedia Development Life Cycle, equipped with level-based challenges, scoring systems, and interactive question checkpoints. Blackbox testing showed all features function properly, and questionnaire data from 20 students indicated positive responses, with an overall satisfaction rate of 87 percent. Novelty: The game integrates platformer mechanics with structured math tasks aligned with early-grade needs. Implications: The product can serve as an alternative digital learning medium that supports engagement and foundational numeracy skills for elementary learners. Highlights: • Platformer-based math learning• Usability proven through blackbox testing• Positive student perception Keyword: Mathematics Game, Unity 2D, Platformer, Educational Media, Elementary Students